Somatic Embryogenesis in the Family Gentianaceae and Its Biotechnological Application - Tomiczak, Karolina; Mikuła, Anna; Niedziela, Agnieszka; Wójcik-Lewandowska, Anna; Domżalska, Lucyna; Rybczyński, Jan J. (Frontiers in Plant Science, 2019)
The family Gentianaceae consists of 1736 species, which play an important role in human being existence due to their pharmacological and horticultural values. Many species accumulate bitter iridoid substances used medicinally and in flavorings, while others are cultivated because of beauty of their flowers showing a wide range of colors and patterns. Out of 99 genera belonging to the gentian family, process of somatic embryogenesis (SE) was reported for 5. The first reports, aimed at micropropagation of ornamental cultivars and production of secondary metabolites, concerned Centaurium erythraea Rafn., Eustoma russellianum Grieseb. and Exacum affine Balf. Somatic embryos were induced on different explants cultured in the liquid Murashige and Skoog medium supplemented with auxins and cytokinins. In the 90s of the last century, significant progress in the exploration of the phenomenon of SE and its biotechnological application was made for the genus Gentiana. The process was induced on various explants and studied at the structural and ultrastructural levels. Regenerated plants were screened for genetic stability using flow cytometry, chromosome counting and molecular markers. Besides typical indirect SE, the use of leaf fragments enabled to obtain single-cell origin of somatic embryos. On the other hand, proliferation of embryogenic callus in liquid medium resulted in the establishment of long-term embryogenic cell suspension cultures, paving the way not only to study the formation of somatic embryos and the development of regenerants but also to preserve the morphogenic potential of cell aggregates by cryopreservation. Cell suspensions re-established after storage in liquid nitrogen maintained their embryogenic character and allowed to obtain somatic embryo-derived regenerants that were true-to-type at both genetic and epigenetic levels. Another application of SE was related to genetic manipulation purposes. Efficient protocols of plant regeneration from callus-, cell suspension- or leaf mesophyll-derived protoplasts allowed engaging procedures of somatic hybridization or protoplast electroporation for gentian genome modifications. Also, high embryogenic potential existing in the numerous gentian species enabled successful Agrobacterium-mediated transformation of G. cruciata L. and G. dahurica Fisch.